2000
DOI: 10.1016/s0741-5214(00)90162-9
|View full text |Cite
|
Sign up to set email alerts
|

Venous thrombosis prophylaxis by inflammatory inhibition without anticoagulation therapy

Abstract: Pretreatment with rPSGL-Ig results in: (1) a significant inhibition of thrombosis and vein wall inflammation; (2) a decrease in vein wall cytokine expression; and (3) a promotion of thrombus resolution. Inflammatory inhibition by rPSGL-Ig without anticoagulation therapy provides effective venous thrombosis prophylaxis in experimental venous thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 23 publications
(31 reference statements)
6
68
1
3
Order By: Relevance
“…Tissue factor and P-selectin appear to both be necessary for thrombus formation and they appear to both be resident on microparticles derived from monocytes, as indicated by the presence of monocyte proteins on the microparticles 19,20 . In a baboon venous stasis model of thrombosis, P-selectin inhibition was found to prevent thrombus development and facilitate clot resolution 24,25 . In most of these models, it is difficult to determine whether the tissue factor-P-selectin involvement in thrombus formation is due to cellular interactions or microparticles 26 .…”
Section: A the Role Of Blood Cells Versus Vascular Contribution To Vmentioning
confidence: 99%
“…Tissue factor and P-selectin appear to both be necessary for thrombus formation and they appear to both be resident on microparticles derived from monocytes, as indicated by the presence of monocyte proteins on the microparticles 19,20 . In a baboon venous stasis model of thrombosis, P-selectin inhibition was found to prevent thrombus development and facilitate clot resolution 24,25 . In most of these models, it is difficult to determine whether the tissue factor-P-selectin involvement in thrombus formation is due to cellular interactions or microparticles 26 .…”
Section: A the Role Of Blood Cells Versus Vascular Contribution To Vmentioning
confidence: 99%
“…In the present study, activated partial thromboplastin, thrombin clotting time, and template bleeding time were not significantly different between saline-treated and rPSGL-Ig (4 mg/kg)-treated animals. 16 …”
Section: Selectin Antagonistsmentioning
confidence: 99%
“…Several animal studies support this hypothesis: In a cat model, a recombinant soluble form of human SELPLG appeared to protect against myocardial ischemic reperfusion injury (Hayward et al 1999); and in a porcine model, recombinant soluble SELPLG-Ig was shown to have a beneficial effect on restenosis (Bienvenu et al 2001). Animal models have also suggested a key role for SELPLG in thrombogenesis, through its implication in the binding of platelets to neutrophils (Eppihimer & Schaub, 2000;Kumar et al 1999;Wakefield et al 2000).…”
Section: Introductionmentioning
confidence: 99%